Pemilikan bersama tanah pusaka : Realiti, masalah dan cabaran / Mohd Marbawi Taha, Jasni Sulong and Mohd Nasir Ayub - Taha, Mohd Marbawi; Sulong, Jasni; Ayub, Mohd Nasir (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
The land of co-proprietorship (TPB) is a piece of land jointly own by several owners. This kind of ownership even though varied upon the value of their specific shares towards the land, but all owners hold the same rights in term of management about the land such as in getting an approval to develop the land, paying quit rents and so on. The disagreement among co-proprietorship of the land would resulted in a conflict in handling such matter. As consequences, the land will remain abandoned and uneconomic as well as will render to disposes by the State Authority for example, for not paying the quit rent. Therefore, the paper will discuss on the existence of TPB from the perspectives of practice and religion, including its negative impacts and solutions to evade from any problems taking place. The type of research is a qualitative research which consists of content analysis towards library materials such as books, statutes, Islamic fatwa as well as interview with experts. The study found out that TPB could be managed by disseminating knowledge among heirs about Islamic law of inheritance, as well as an earlier plan by the owner upon land distribution after his demise and proper arrangement among them. In addition, the State Authority should take a firm pace in handling TPB registration in order to avoid unnecessary co-proprietorship. It is believed that if the suggestions are fully observed, the negative impacts of TPB will be prevented and hence possession of land would benefit every holder and heirs as well as productivity of the land will be well managed.